Safety and efficacy of a purified canine immunoglobulin G formulation for treatment of 76 cats clinically affected by the Australian paralysis tick (Ixodes holocyclus). Issue 10 (4th July 2022) - Padula, AM
Abstract : Acute adverse reactions in cats administered unrefined canine paralysis tick ( Ixodes holocyclus ) antiserum are commonly observed by veterinarians and can lead to significant morbidity and potentially fatal. A purified antiserum canine IgG concentrate was chromatographically prepared and aseptically formulated in single doses containing the equivalent of 5 mL of unrefined tick antiserum (TAS). The IgG was used for slow intravenous infusion into clinically affected cats at multiple veterinary clinics on the eastern seaboard of Australia. Overall, 72/76 (95%) of cats survived hospital discharge, an efficacy comparable to published data. A subset of 22 cats previously treated with unrefined TAS and considered high risk were included in the dataset. The safety profile was excellent with 0/76 acute adverse reactions although 2/76 (2.6%) developed mild facial swelling within 2 h of infusion that responded to the antihistamine. In conclusion, cats intravenously infused with purified IgG from canine TAS did not exhibit the expected frequency of acute adverse reactions during infusion and it was both safe and effective for the treatment of tick paralysis in cats.